Optimizing the Management of the Indonesian State Budget in a Sharia Perspective: Theoretical Review and Policy Recommendations - Gozaly, Ahmad Yusdi; Janwari, Yadi; Hasanuddin, Muhammad; Athoillah, Mohamad Anton (CV. Strata Persada Academia, 2025)
The management of the State Budget (APBN) is a key instrument in fiscal policy, playing a crucial role in achieving economic growth, price stability, and income distribution. However, in recent years, Indonesia’s APBN management has faced various challenges, including a continuously increasing budget deficit, suboptimal expenditure efficiency, and limited state revenue sources. To address these issues, the Islamic economic perspective offers an alternative approach that emphasizes justice, transparency, and sustainability in public financial management. This study employs a descriptive qualitative method through a literature review to analyze APBN management based on Islamic economic principles. The findings indicate that the implementation of Sharia-compliant financial instruments, such as zakat, waqf, and sukuk, can reduce reliance on interest-bearing debt while sustainably increasing state revenue. Furthermore, applying transparency, accountability, and efficiency principles in APBN management in accordance with Sharia values can enhance public trust in the government and Islamic financial institutions. Optimizing APBN management from a Sharia perspective requires strengthening Islamic financial literacy, improving the capacity of zakat and waqf management institutions, and harmonizing regulations that support the integration of Sharia financial instruments into the national fiscal system. Through a more just and sustainable approach, Indonesia can achieve more effective budget management and promote inclusive and competitive national development.